Final disposal of radioactive waste - Freiesleben H. (EPJ Web of Conferences, 2013)
In this paper the origin and properties of radioactive waste as well as its classification scheme (low-level waste – LLW, intermediate-level waste – ILW, high-level waste – HLW) are presented. The various options for conditioning of waste of different levels of radioactivity are reviewed. The composition, radiotoxicity and reprocessing of spent fuel and their effect on storage and options for final disposal are discussed. The current situation of final waste disposal in a selected number of countries is mentioned. Also, the role of the International Atomic Energy Agency with regard to the development and monitoring of international safety standards for both spent nuclear fuel and radioactive waste management is described.